PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN IKLIM ORGANISASI SEBAGAI VARIABEL INTERVENING (STUDI PADA KANTOR DUKCAPIL KOTA MATARAM) - khairul Amri; Zainal Abidin; Siti Nurmayanti (Master of Management, Mataram University, 2017)
This study aims to analyze the influence of Transformational Leadership on OCB, to analyze the influence of Transformational Leadership on Organizational Climate, to analyze the influence of Organizational Climate on OCB, to analyze the Climate of Transformational Leadership Mediation Organization against OCB. This research was conducted at Population and Civil Registration District Agency Of Mataram with 45 people as a sample using saturated sampling technique that is sample determination technique when all member of population used as sample. The type of this research was associative causal research and data collection tool was Analysis PLS-SEM. The results of the data analysis shows that, transformational leadership has a positive and significant effect on OCB. The Climate Organization has a positive and significant impact on OCB. Transformational leadership has a positive and significant influence on the Climate of the Organization. Transformational leadership has a positive and significant impact on OCB through the Climate of the Organization. Keywords: Transformational Leadership, Organizational Climate and OCB.